2017
DOI: 10.1002/app.45438
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation‐grafting surface modification of waste silicone rubber composite insulator powder: Characterizations and properties of EPDM/modified waste powder composites

Abstract: In order to broaden the applications of waste silicone rubber composite insulator powder (WSP), modified waste powder (WSP-KH570) was prepared by a two-step treatment process involving improved surface oxidation approach by using acidic H 2 O 2 solution and subsequently grafting of KH570. Fourier transform infrared spectroscopy in the attenuated total reflection mode (FTIR-ATR) analysis revealed the presence of KH570 on the powder surface. The result was confirmed by thermogravimetric analysis (TGA). Blends of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…[7][8][9] Currently, two methods, chemical degradation and physical pulverization, are commonly used for industrial recycling of discarded SCIs. [10][11][12] The chemical degradation method is complex and inefficient, requires specific catalysts, and induces secondary pollution. [13][14][15] For the physical pulverization method, crumb SCIs are further ground into fragmented products and subsequently refined to obtain fine silicone rubber powders (SRPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Currently, two methods, chemical degradation and physical pulverization, are commonly used for industrial recycling of discarded SCIs. [10][11][12] The chemical degradation method is complex and inefficient, requires specific catalysts, and induces secondary pollution. [13][14][15] For the physical pulverization method, crumb SCIs are further ground into fragmented products and subsequently refined to obtain fine silicone rubber powders (SRPs).…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Previous studies have demonstrated that pretreatment of SRPs with various types of coupling agents is a practical method for addressing this issue. [12,[23][24][25] Therefore, most of the SRP surface modification processes reported to date involve two critical steps, the oxidation of the Si-CH 3 moieties into silanol (Si-OH) groups, which are subsequently subjected to silylation reactions with coupling agents to introduce desired surface functionalities. Several methods have been proposed for the surface oxidation of SRPs, including plasma, ozone-ultraviolet radiation, and acid oxidation treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical treatments are another alternative for rubber recycling purposes (Sun et al, 2017), after treating waste silicone rubber composite insulator with H 2 O 2 combine with graphite in an acid medium, obtained a material with better mechanical and thermal properties (Sun et al, 2017). Sulfuric acid has been used to treat crumb rubber in combination with ultraviolet light, as a result, the rubber's stiffness increased (Alawais and West, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[ 21–24 ] After reviewing the literature, it can be found that nitric acid, sulfuric acid, chlorination, KH550, stearic acid, PVC, LDPE, LLDPE, HDPE, hydrogen peroxide, and twin‐screw extruder are mainly used to activate the waste rubber powder. [ 25–28 ] For example, Avraam I. Isayev et al used a new ultrasonic twin‐screw extruder to perform ultrasonic devulcanization activation of 10 mesh and 30 mesh tire rubber particles. The results showed that the desulfurization activation of 30 mesh rubber was higher than that of 10 mesh rubber, and the revulcanization product of 30 mesh rubber exhibited higher elongation at break and lower viscosity.…”
Section: Introductionmentioning
confidence: 99%